Analisis Implementasi Kurikulum Merdeka PAUD Di Kabupaten Sleman - Nur Cholimah Nur; Aliyah Latifah Hanum (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2023)
Lecturer program activities outside the campus aims to develop independent curriculum-based learning tools for PAUD teachers who are members of the Sleman Regency PAUD Forum. This activity was carried out in several stages, namely conducting a needs analysis for PAUD teachers in Sleman Regency, designing a training program for developing independent curriculum-based learning tools and practicing making learning tools. The training materials for teachers include; a) development of learning outcomes, learning objectives, and PAUD learning objectives, b) creation of P5 and intracurricular teaching modules, d) use of loose parts in learning, d) independent assignments to develop teaching modules based on the Independent Curriculum, and e) evaluation of module creation independent curriculum-based teaching. The practical results of the training were that 14 participants were able to create P5 modules and 16 participants were able to create intracurricular modules. Four P5 teaching modules and five best intracurricular teaching modules were awarded. In making the P5 or intracurricular teaching modules encountered obstacles experienced by teachers including; determine the main theme, use the assessment, and provide a starting sentence for the children in the module. So it was concluded based on the results above that the independent curriculum-based learning development training activities had an impact on the knowledge and skills of PAUD teachers who were members of the Sleman Regency PAUD Forum.